Preventing the preventable: Assessing the burden of incessant caesarean deliveries in select Indian states using NFHS-5 - Punit Mishra; Retna Sheeja Pushpa Raj; Aditi Aditi; Muthusamy Sivakami (PLoS ONE, 2025)
The World Health Organization (WHO) recommends that life-saving Caesarean sections (CS) should account for 10–15% of deliveries. Southern states of India have good obstetric facilities and better public health systems than other parts of India. However, CS rates in select states are considerably higher. This study examines the prevalence and determinants of preventable CS among mothers in select Indian states, specifically the states that have high institutional deliveries (>95%) viz. Andhra Pradesh, Kerala, Karnataka, and Tamil Nadu. It further compares the complications faced by CS and vaginal delivery cases. Data has been derived from a cross-sectional survey, the National Family Health Survey-5. Bivariate and Logistic regression analyses were used. The main outcome measured is Preventable C-sections, defined as per conditions in Robson’s criteria of 10-group classification based on obstetric characteristics for a woman. Results show that the preventable CS rates in these selected states were much higher than at the national level. Key correlates were higher education and middle socioeconomic status. The study highlights the need for policy reforms, maternal education, and healthcare system improvements to reduce unnecessary CS in select states of India, where the health system is exceptionally good but , have another health burden in form of demand for unnecessary caesarean deliveries.